Equity Interest Scheme in Polymetallic Nodules Deep Seabed Mining: The Positives and Negatives - Agustina Merdekawati; I Made Andi Arsana (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2022)
UNCLOS 1982 initially obliged all applicants to submit a reserved area when applying for exploration activities in the Area. Such provisions were derogated when the equity interest scheme was introduced in the exploration regulations for polymetallic sulphides and cobalt-rich ferromanganese crust. The applicant may choose to submit a reserved area or offer an equity interest in a joint venture with the Enterprise. There has been a push to implement the same policy for polymetallic nodule (PMN) explorations. Although this prospect has sparked much support and rejections, there have been no scholarly articles substantiating such alignment's positive and negative impacts. Applying the scheme for all three types of minerals may significantly impact the implementation of the common heritage of mankind principle in the Area. This article normatively assesses the prospect of incorporating the equity interest scheme into the PMN utilization regime to identify its advantages and disadvantages compared to the reserved area scheme. The study found that incorporating the equity interest scheme for PMN would be oriented to optimize the financial benefits. However, it would further compromise the access for developing countries.